Sistem Monitoring Prestasi Akademik dan Aktivitas Siswa Dengan Metode Weterfall (Studi Kasus : SDI Al Azhar 17 Bintaro) - Ryko Krisdianto; Maulana Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Monitoring and assessment activities are the main activities in the world of education. However, these activities can’t be implemented optimally. Parents still have difficulty monitoring their children's learning activities at school. Notification of student achievement (grades) is only done at the time of the final report’s reception. Parents can only get the final result of their children’s learning activities without being able to monitor their children’s learning process. Notification of administrative issues (education donations, books, etc) is usually notified before the reception of report cards. In addition, assessment is still done manually, as a result, parents, and students still difficult to know the grades and results of the learning process at the time. Therefore, we need a system that facilitates the process of monitoring and assessment of students, both for teachers and parents to overcome this problem. The research aims to develop a student assessment and monitoring system. The methods to develop this system are data collection, hardware and software analysis, system design and analysis, and system implementation and testing. The result of this research is a system that can help teachers to manage student grades, and facilitate the parents to monitor and get information about their children’s learning activities.